Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(+) TH1 : -1 >=x ta có
E = l x - 3l + lx + 1l = 3-x + ( -x - 1) = 3- x - x - 1 = 2 - 2x
(+) TH2 -1< x <= 3 ta có
E = 3 - x + x + 1 = 4
(+) TH3 x> 3 ta có:
E = x - 3 + x + 1 = 2x - 2
+ Nếu x < -3, ta có:
3(x - 1) - 2|x + 3| = 3(x - 1) - 2(-3 - x)
= 3x - 3 + 6 + 2x
= 5x + 3
+ Nếu \(x\ge-3\) ta có:
3(x - 1) - 2|x + 3| = 3(x - 1) - 2(x + 3)
= 3x - 3 - 2x - 6
= x - 9
A = 4.( x - 3) - 3|x + 3|
- Nếu x > -3 ta có A = 4.(x - 3) - 3.(x + 3) = 4x - 12 - 3x - 9 = x - 3
- Nếu x < -3 ta có A = 4.(x - 3) - 3.(-x - 3) = 4x - 12 + 3x + 9 = x + 21
B = 2.|x + 1| - |x - 1|
- Nếu x > 1 thì B = 2.(x + 1) - (x - 1) = 2x + 2 - x + 1 = x + 3
- Nếu x = 0 thì B = 2.(0 + 1) - (0 - 1) = 2 - (-1) = 3
- Nếu x < 0 thì B = 2.(-x - 1) - (-x + 1) = -2x - 2 + x - 1 = -x - 3
|x+1|+|x+3|
*)Nếu x>-1
=>|x+1|+|x+3|=x+1+x+3=2x+4
*)Nếu -3<x<-1
=>|x+1|+|x+3|=x+1-x-3=-2
*)Nếu x<-3
=>|x+1|+|x+3|=-x-1-x-3=-2x-4